Home - Coben, Harlan, 1962- (New York : Dutton, an imprint of Penguin Random House LLC, 2016)
A decade ago, kidnappers grabbed two boys from wealthy families and demanded ransom, then went silent. No trace of the boys ever surfaced. For ten years their families have been left with nothing but painful memories and a quiet desperation for the day that has finally, miraculously arrived: Myron Bolitar and his friend Win believe they have located one of the boys, now a teenager.
Keywords: Bolitar, Myron (Fictitious character) -- Fiction; Sports agents -- Fiction; Missing children -- Fiction